EXPLAINABLE AI PADA CHATBOT MODERN : REVIEW ALGORITMA INTERPRETABILITAS UNTUK MENJELASKAN PROSES PENGAMBILAN KEPUTUSAN MODEL - David Mahlon Sarumaha; Putu Pramudya Pratama; Ganesha Setiawan (CV. Denasya Smart Publisher, 2025)
Large Language Models (LLMs) have transformed modern chatbots into systems capable of natural interaction and understanding conversational context across various domains, such as education, healthcare, and customer service. However, this advancement presents a major challenge in the form of a